2021
DOI: 10.3389/fnins.2021.670475
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Predicting Individual Severity of Blepharospasm Using Diffusion Tensor Imaging

Abstract: Accumulating diffusion tensor imaging (DTI) evidence suggests that white matter abnormalities evaluated by local diffusion homogeneity (LDH) or fractional anisotropy (FA) occur in patients with blepharospasm (BSP), both of which are significantly correlated with disease severity. However, whether the individual severity of BSP can be identified using these DTI metrics remains unknown. We aimed to investigate whether a combination of machine learning techniques and LDH or FA can accurately identify the individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…The results of the present study showing changes in specific white matter tracts expand previous literature on CD and BSP, demonstrating diffuse microstructural damage in the basal ganglia, cerebellum and sensorimotor cortical areas [ 10 , 11 , 12 , 13 ], as well as in the white matter [ 11 , 19 , 20 , 51 , 52 ]. Moreover, the WM tracts we reconstructed correspond to brain regions with microstructural integrity loss in the WM adjacent to the pallidum and putamen and the precentral and postcentral gyri [ 13 , 17 , 53 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of the present study showing changes in specific white matter tracts expand previous literature on CD and BSP, demonstrating diffuse microstructural damage in the basal ganglia, cerebellum and sensorimotor cortical areas [ 10 , 11 , 12 , 13 ], as well as in the white matter [ 11 , 19 , 20 , 51 , 52 ]. Moreover, the WM tracts we reconstructed correspond to brain regions with microstructural integrity loss in the WM adjacent to the pallidum and putamen and the precentral and postcentral gyri [ 13 , 17 , 53 ].…”
Section: Discussionsupporting
confidence: 87%
“…Microstructural alterations were also found in the white matter (WM) adjacent to the primary sensorimotor, inferior parietal and middle cingulate cortices in patients with CD [ 13 , 14 , 15 ] and BSP [ 16 , 17 , 18 ]. Finally, studies with whole-brain approaches showed WM microstructural disruption in the corpus callosum, the internal capsule and the white matter underlying the sensorimotor cortex in CD and BSP patients [ 11 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…LDH is independent of the diffusion model and can reveal intervoxel diffusion properties by capturing the overall coherence of water molecule diffusion within a neighbourhood; it reflects the microstructural coherence of the underlying WM fibres and provides additional insights beyond traditional intravoxel metrics. Some recent studies have applied LDH parameters to the detection of WM microstructure abnormalities in vascular cognitive impairment [ 15 ], epilepsy [ 16 ], type 2 diabetes [ 17 ], and blepharospasm [ 18 ], demonstrating regions of variation that differed from those of intravoxel diffusion metrics. Moreover, LDH can help predict the prognosis of stroke patients [ 19 ].…”
Section: Introductionmentioning
confidence: 99%